ANALISIS PRODUKTIVITAS PONDASI TIANG PANCANG PROYEK PEMBANGUNAN GEDUNG SMKN KEHUTANAN PEKANBARU - Lidya Birahmatika; Winayati; Fitridawati Soehardi (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The construction project of the Pekanbaru Forestry Vocational High School building complex is planned with 330 calendar days in each job, it is necessary to carry out a productivity analysis to determine the level of productivity so that the work can run within the planned time. The first step in a building is foundation work, weather constraints, machine piles, damaged location access, the use of time study methods or knowing the time chosen to analyze productivity. The study was conducted by collecting data based on field observations to obtain the data needed to analyze the productivity of pile foundation work and comparison with the index value of the work unit price analysis on the 2016 Indonesian National Standard which refers to the Regulation of the Minister of Public Works and Public Housing number 28/PRT/M/2016 (National Index) concerning the coefficient of pile foundation work. Observations were made during the duration of the piling foundation work, namely 5 working days starting on 8, 9, 10, 12, and 15 March 2021. Based on the analysis that has been carried out, it can be concluded that the lowest field index value was obtained on the implementation of the piling work on the 15th. March 2021, which is 0.010 for the highest productivity obtained on March 9, 2021, with a productivity value of 0.056. So that the total field index value is 0.1221 which has a difference of 0.0021 from the pile foundation work index value that has been set in the national index which is 0.1200.